Activation of the brain melanocortin system is required for leptin-induced modulation of chemorespiratory function - Bassi, M. [UNESP]; Nakamura, N. B. [UNESP]; Furuya, W. I. [UNESP]; Colombari, D. S. A. [UNESP]; Menani, Jose Vanderlei [UNESP]; Carmo, J. M. do; Silva, A. A. da; Hall, J. E.; Colombari, E. [UNESP] (Wiley, 2015)
Abstract: Melanocortin receptors (MC3/4R) mediate most of the metabolic andcardiovascular actions of leptin.Aim: Here, we tested if MC4R also contributes to leptin’s effects on respi-ratory function.Methods: After control measurements, male Holtzman rats received dailymicroinjections of leptin, SHU9119 (MC3/4R antagonist) or SHU9119combined with leptin infused into the brain lateral ventricle for 7 days.On the 6th day of treatment, tidal volume (VT), respiratory frequency (fR)and pulmonary ventilation (VE) were measured by whole-body plethys-mography during normocapn ia or hypercapnia (7% CO2). Baseline meanarterial pressure (MAP), heart rate (HR) and metabolic rate were alsomeasured. VE, VTand fRwere also measu red in mice with leptin receptordeletion in the entire central nervous syst em (LepR/Nestin-cre) or only inproopiomelanocortin neurones (LepR/POMC-cre) and in MC4R knockout(MC4R/) and wild-type mice.Results: Leptin (5 lgday1) reduced body weight (~17%) and increasedventilatory response to hypercapnia, whereas SHU9119 (0.6 nmol day1)increased body weight (~18%) and reduced ventilatory responses comparedwith control-PBS group (Lep: 2119  90 mL min1kg1and SHU9119:997  67 mL min1kg1, vs. PBS: 1379  91 mL min1kg1). MAPincreased after leptin treatment (130  2 mmHg) compar ed to PBS(106  3 mmHg) or SHU9119 alone (109  3 mmHg). SHU9119 pre-vented the effects of leptin on body weight, MAP (102  3 mmHg) andventilatory response to hypercapnia (1391  137 mL min1kg1). Theventilatory response to hypercapnia was attenuated in the LepR/Nestin-cre,LepR/POMC-cre and MC4R/mice.Conclusion: These results suggest that central MC4R mediate the effectsof leptin on respirat ory response to hypercapnia.Keywords blood pressure, central chemoreception, hypercapnia, leptin,MC3/4 rece ptor, melanocortin system.